Design and Implementation of Adiabatic Sequential and Combinational circuits using Reversible Gate - Yadav, Bhawna; Varma, Tarun (International Journal of Computer Sciences and Engineering, 2019)
Programmable reversible logic circuit (RLC) is design style for nanotechnology and quantum computing with minimum heat generation, quantum cost and garbage output. Late advances in reversible rationale utilizing and quantum PC calculations consider enhanced PC engineering and math rationale unit plans. In this paper, we survey the N-bit reversible logic adder and sub tractors are used with minimal delay, and may be configured to produce a variety of logical calculations. The reversible N-bit adder/ sub tractor design is verified and its advantages over the only existing adder design are quantitatively analyzed.